2017
DOI: 10.1039/c7ra08029h
|View full text |Cite
|
Sign up to set email alerts
|

Arsenene/Ca(OH)2 van der Waals heterostructure: strain tunable electronic and photocatalytic properties

Abstract: Based on ab initio calculations, we identify that the arsenene/Ca(OH)2 van der Waals heterostructure is an indirect-band-gap semiconductor and find that its electronic and photocatalytic properties can be continuously tuned by external strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Furthermore, the ground-state structural properties of the heterostructures are nearly identical, leading to similar electronic and optical properties regardless of the stacking order (see the Supporting Information for details: Table S1 and Figure S1). Similar behaviors are also found in germanene/BeO heterostructures and arsenene/Ca­(OH) 2 heterostructures . Thus, in the following sections, we take the β-stacking BlueP/Mg­(OH) 2 heterostructure as a representative to show our results.…”
Section: Results and Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the ground-state structural properties of the heterostructures are nearly identical, leading to similar electronic and optical properties regardless of the stacking order (see the Supporting Information for details: Table S1 and Figure S1). Similar behaviors are also found in germanene/BeO heterostructures and arsenene/Ca­(OH) 2 heterostructures . Thus, in the following sections, we take the β-stacking BlueP/Mg­(OH) 2 heterostructure as a representative to show our results.…”
Section: Results and Discussionsupporting
confidence: 57%
“…42 Strain engineering is a feasible avenue to tune the band gap and band-edge positions, which has been exemplified by many studies for different materials. 11,13,14,42 The evolutions of the band gap and band-edge position of the BlueP/Mg(OH) 2 vdW heterostructure with strain are displayed in Figure 4a,b, respectively, together with the strain energy. It is found that the band gap slowly decreases with the tensile strain increasing (up to 10%) and then drops sharply for strains beyond 10%, while it quickly decreases with the increasing compressive strain, as shown in Figure 4a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Tensile strains can be applied to tune the band edge positions and optical absorption for a better match with the redox potentials of water and the solar spectrum, such that the Arsenene/Ca(OH) 2 heterostructure could also become a promising photocatalyst for water splitting. 313 The effect of germanene and Ge(111) substrates on the electronic properties of antimonene monolayer was investigated within DFT. 46 Antimonene overlayers on metal or semiconductor substrates have been also actively investigated.…”
Section: Substrate Effectsmentioning
confidence: 99%
“…In addition, the predicted optical absorbance attains to the maximum absorption of 25% for ML SiN and GeN, which are comparable with that of reported photocatalysts arsenene/ Ca(OH) 2 heterostructure. 60 With appropriate band edges and high optical absorbance, ML SiN and GeN have promising potential to be optoelectronics devices and used in photocatalytic water splitting.…”
Section: Photocatalysismentioning
confidence: 99%